2011
DOI: 10.1007/s11258-011-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant competitive ability and the transitivity of competitive hierarchies change with plant age

Abstract: Plant competitive effect and response ability are known to change with plant age, however it remains unclear how competitive hierarchies among plant species change as plants age and transition between life stages. We examined the competitive interactions among seven species in all pairwise combinations in a greenhouse experiment. Competitive effect and response were measured as the relative yield (RY) for each target-neighbor species combination for both seedling and adult plants. Competitive hierarchies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…It has been argued that strong intransitivity may not easily occur in nature as it requires the three species involved to be present simultaneously (e.g. Gallien et al., ; but see Stouffer et al., ; Zhang & Lamb, ). In this special feature, Gallien et al.…”
Section: How Do Intransitive Competition Network Assemble?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that strong intransitivity may not easily occur in nature as it requires the three species involved to be present simultaneously (e.g. Gallien et al., ; but see Stouffer et al., ; Zhang & Lamb, ). In this special feature, Gallien et al.…”
Section: How Do Intransitive Competition Network Assemble?mentioning
confidence: 99%
“…It has been argued that strong intransitivity may not easily occur in nature as it requires the three species involved to be present simultaneously (e.g. Gallien et al, 2017; but see Stouffer et al, 2018;Zhang & Lamb, 2012). In this special feature, Gallien et al (2018) explore a potential mechanism by which initially weak intransitive competition could strengthen through time.…”
Section: How Do Intr Ans Itive Compe Titi On Ne T Work S a Ss Emb Le?mentioning
confidence: 99%
“…The hypothesis of competitive intransitivity (Gilpin, 1975) has regained attention among ecologists as new empirical approaches (Soliveres et al, 2011;Zhang & Lamb, 2012) and analytical tools (Rojas-Echenique & Allesina, 2011;Ulrich, Soliveres, Kryszewski, Maestre, & Gotelli, 2014) have revealed complex competitive interactions in multi-species ecological communities (Allesina & Levine, 2011;Engel & Wetzin, 2008;Gallien, 2017). Here, intransitivity refers to loops in the hierarchy of competitive interactions in which species A is superior to species B, B is superior to C and C is superior to A.…”
Section: Introductionmentioning
confidence: 99%
“…Westoby, Falster, Moles, Vesk, & Wright, 2002;Paine, Baraloto, Chave, & Herault, 2011; but see Kusumoto et al, 2016 andGallien, 2017), and this separation of species in trait space may generate sufficient niche differentiation to permit species coexistence (Adler, Fajardo, Kleinhesselink, & Kraft, 2013). However, a different although not mutually exclusive explanation for the observed degree of coexistence is that the mix of competitively counteracting traits, such as root and shoot competition (Zhang & Lamb, 2012), or complementary resource use (Yachi & Loreau, 2007), generates a dynamic balance of competitive strength through ICNs, which allows for species coexistence in spite of high niche overlap. Thus, we interpret ICNs as a cause, not an effect, of high species richness.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms will have an impact on the competitive ability of each plant later in the cycle. Zhang and Lamb (2012) found that early differences between species for competitive effect did not vary substantially with plant age. As suggested by Fayaud et al (2014), a better understanding of early growth in intercrop systems could help to adapt management practices to attain specific objectives, such as proper proportion of each species in terms of grain yield.…”
Section: Discussionmentioning
confidence: 86%